Global trends in resistance studies of gemcitabine and pancreatic cancer: a bibliometric and visual analysis from 2010 to 2024 - Gu, Dandan; Huang, Shaoyang; Zhao, Kai; Zhang, Xiaohong; Zhang, Jinjing; Xiong, Wei (Frontiers in Pharmacology, 2025)
IntroductionPancreatic adenocarcinoma (PC) represents a prevalent and highly aggressive malignancy within the digestive system, characterized by an exceedingly poor prognosis and a dismal 5-year survival rate of below 7%. Gemcitabine (GEM) remains the cornerstone chemotherapeutic agent in the management of PC; however, the growing challenge of GEM chemoresistance, which undermines treatment efficacy, represents a significant obstacle in clinical practice. To date, no comprehensive bibliometric analysis has been undertaken to systematically explore studies on GEM resistance in the context of PC. This study aims to deliver a thorough evaluation of the research hotspots pertaining to GEM resistance in PCs.MethodA systematic search was conducted for articles published from 1 January 2010, to 15 December 2024, focusing on resistance studies of GEM in PC. Bibliometric analysis and visualization were performed utilizing VOSviewer and CiteSpace tools, applied to literature data extracted from the Web of Science Core Collection (WoSCC).ResultsBetween 2010 and 2024, a total of 2,689 papers were published across 472 institutions in 74 countries, reflecting a consistent upward trajectory in annual publication output. China and Fudan University emerged as the leading contributors to the research output on this topic, representing the most prolific country and institution, respectively. Giovannetti, Elisa, and Yu, Xianjun are the most prolific scholars in this field. Cancer Research stands out as the most cited and impactful journal, while research on the tumor microenvironment, targeted therapy, and circular RNA has emerged as a key focus area in recent years.ConclusionThis study provides a systematic and comprehensive overview of the literature on GEM resistance in PC over the past 15 years. This analysis offers scholars critical insights into the field from a bibliometric perspective, potentially informing future studies on the development of chemotherapeutic treatments for PC.